FRANK STELLA AND HIS THREE-DIMENSIONAL OBJECTS - BULDUK, Bülent (Atlas Journal, 2018)
The first quarter of the 20thcentury is characterized as a period of avant-garde manifestations that shaped the future of Western art. Art movements such as Cubism, Futurism, Dadaism, and so forth have radically opposed traditional art. Issues like the shift in ways of seeing, the object-oriented insights of art, and the inclusion of concept into art praxes have been the breaking points of this period. Many artists and art movements in 1960shave transformed this legacy positively as far as it could go. Minimalism, one of the significant art movements of this era, is based on the ideathat“less is more”. Minimalism has made use of this idea successfully in order to create three-dimensional objects. Frank Stella, a prominent member of this movement, has personalized Minimalism’s reductionist and simple language via his special objects, which he has integrated into space. Stella, who started by criticizing the extremely personal gestures of abstract expressionism, has produced artworks that can be categorized neither as painting nor sculpture.